Determinants of Current Account Balance in ASEAN+6 - Dewi Purnama; Budiono Budiono; Anhar Fauzan Priyono (Jurnal Economia, 2021)
Abstract: The phenomenon of global current account imbalance has made researchers and policy makers provide more attention on current account issues. This phenomenon is illustrated by the US' current account deficit which continues to increase, while ASEAN+6 reaps a surplus. This study aims to study the factors that affect the aggregate current account in ASEAN+6 that have not been explained by previous studies. Based on the dynamic panel model (GMM) used, it was found that the variables Lagged-current account, ToT, Exchange Rate Stability, and Household Consumption have a significant effect on the aggregate current account in ASEAN+6. On the other hand, the REER and Government Expenditures do not have a significant effect on the ASEAN+6 current account. The benefit of this research is that it can be used for the formulation of current account policies to minimize the government's efforts to overcome a bigger issue: imbalance in balance of payment.Keywords: Current account balance, Generalized Method of Moment, ASEAN+6 Determinan Neraca Transaksi Berjalan di ASEAN+6Abstrak: Fenomena ketidakseimbangan transaksi berjalan global telah membuat para peneliti dan pembuat kebijakan memberikan perhatian lebih pada masalah transaksi berjalan. Fenomena ini tergambar dari defisit transaksi berjalan AS yang terus meningkat, sedangkan ASEAN+6 menuai surplus. Penelitian ini bertujuan untuk mempelajari faktor-faktor yang mempengaruhi neraca transaksi berjalan agregat di ASEAN+6 yang belum dijelaskan oleh penelitian-penelitian sebelumnya. Berdasarkan model panel dinamis (GMM) yang digunakan, ditemukan bahwa variabel Lagged-current account, ToT, Exchange Rate Stability, dan Household Consumption berpengaruh signifikan terhadap agregat current account di ASEAN+6. Di sisi lain, REER dan Belanja Pemerintah tidak berpengaruh signifikan terhadap transaksi berjalan ASEAN+6. Manfaat dari penelitian ini adalah dapat digunakan untuk perumusan kebijakan transaksi berjalan untuk meminimalkan upaya pemerintah mengatasi masalah yang lebih besar: ketidakseimbangan neraca pembayaran.Kata kunci: Neraca transaksi berjalan, Generalized Method of Moment, ASEAN+6